AKSELERASI PENGISIAN DAN VALIDASI DATA LAPORAN INDIKATOR KINERJA KUNCI (IKK) DI BPKAD KE DALAM PORTAL SATU DATA SUMATERA SELATAN - Ahmad Tri Wahyudi; Muhammad Nasir; Jemakmun Jemakmun; Andri Andri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This community service article describes the acceleration process of inputting and validating Key Performance Indicator (IKK) data at the Regional Finance and Asset Management Agency (BPKAD) of South Sumatra Province into the South Sumatra One Data Portal. BPKAD, as the steward of IKK 4.b.3, faces challenges in ensuring the accuracy, validity, and timeliness of budget realization data for Mandatory Basic Public Service expenditures. The implementation of this service activity was carried out through data collection assistance from financial systems (SIMDA and SIPD), cross-data validation assistance, Microsoft Excel-based data processing, and data upload into the One Data Portal using electronic signatures certified by BSrE-BSSN. The service activities resulted in IKK 4.b.3 achievement of 76.98% with a budget realization of IDR 4,037,023,860,288.94 from an allocation of IDR 5,244,085,538,092.00 for Fiscal Year 2025. This program improved data quality, accelerated reporting timelines, and enhanced accountability in regional government performance data management. The activity also contributed to strengthening the implementation of the One Data Indonesia policy at the provincial level.